2009
DOI: 10.1007/s11325-009-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of the impact of oral appliance therapy on the temporomandibular joint during treatment of obstructive sleep apnea: long-term evaluation

Abstract: We conclude that long-term usage of an OA does not cause impairment to the temporomandibular joint. The Helkimo and otologic indexes are simple and useful in long-term patient follow-up. There was a long-term improvement in the ESS values over the years analyzed. A follow-up program could increase compliance by motivating patients to use the device regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 32 publications
(54 reference statements)
4
40
0
6
Order By: Relevance
“…46,91,103,107 However, in an MRI study, translation of the condyle with OA therapy was equal or less than that observed with maximum jaw opening with no significant TMJ morphological alterations observed. 91 Nonetheless, when compared with CPAP therapy, more subjects were found to experience TMD related pain in the initial stages of treatment.…”
Section: Temporomandibular Disordersmentioning
confidence: 83%
See 1 more Smart Citation
“…46,91,103,107 However, in an MRI study, translation of the condyle with OA therapy was equal or less than that observed with maximum jaw opening with no significant TMJ morphological alterations observed. 91 Nonetheless, when compared with CPAP therapy, more subjects were found to experience TMD related pain in the initial stages of treatment.…”
Section: Temporomandibular Disordersmentioning
confidence: 83%
“…102 Overall, there appears to be a decrease in intensity of TMD pain with continued OA use. 90,100,102,106,107 To date, only two studies have addressed the issue of TMD related pain and occlusal function associated with OA use. 108,109 Both these studies advocated the use of mandibular jaw exercises to manage side effects.…”
Section: Temporomandibular Disordersmentioning
confidence: 99%
“…However, most studies reported that these adverse symptoms that appear in the initial phase of treatment are transient in a large number of affected patients, and there appears to be a trend of symptoms to decrease over time in the majority of patients. One study reported an improvement in TMD signs and symptoms in some patients undergoing MAD therapy for OSA (Giannasi et al, 2009). In another study, the prevalence of orofacial pain increased with the use of MAD; however this study was based on a single question broad questionnaire and hence the results should be interpreted with caution (Vuorjoki-Ranta, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Two different devices were used: the Monobloc and the Herbst. Giannasi et al, 2009 Treatment adherence could not be objectively verified. Patients reported wearing the appliance at least 4 nights a week.…”
Section: 5%mentioning
confidence: 99%
“…En otra publicación de series de casos de Giannasi et al (2009), se usó el método diagnóstico de Helkimo (Anamnestic Dysfunction Index) y se concluyó que el uso a largo plazo de DAM para pacientes con bruxismo y SHAOS no agravan los síntomas de TTMS, por el contrario, los alivió en los casos que los pacientes presentaban TTMs moderados.…”
Section: Discussionunclassified